Minority Carrier Annihilation at Crystalline Silicon Interface in Metal Oxide Semiconductor Structure. Issue 1666 (3rd November 2014) - Furukawa, Jun; Shigeno, Satoshi; Yoshidomi, Shinya; Node, Tomohito; Hasumi, Masahiko; Sameshima, Toshiyuki; Mizuno, Tomohisa
ABSTRACT: We report photo induced minority carrier annihilation at the silicon surface in a metal–oxide–semiconductor (MOS) structure using 9.35 GHz microwave transmittance measurement. 7 Ωcm n-type 500-μm-thick crystalline silicon substrate coated with 100-nm-thick thermally grown SiO2 layers was used. 0.2-cm-long Al electrode bars were formed at the top and rear surfaces. 635 nm light illumination onto the top surface caused photo induced carriers to be in one side of the silicon region of the Al electrode. Microwave transmittance system detected photo induced carriers diffused from the light illuminated region via the MOS structured region. When the bias voltage was applied at +2.0 and -2.2 V to the electrode at the top surface, the surface recombination velocity increased from 44 (initial) to 83 and 86 cm/s, respectively because of depletion region formation at rear and top surface respectively. Those voltage applications caused change in the distribution of photo induced carriers in a 0.6-cm-wide region including light illuminated, MOS structured, microwave irradiated regions.